Clinically defining the opioid-exposed birthing person and infant as a dyad to support bedside care, surveillance, and research - Jilani, Shahla M.; Davis, Jonathan M.; Goldstein, David; Grossman, Matthew; Jansson, Lauren M.; Terplan, Mishka; Jones, Hendrée E. (Frontiers in Pediatrics, 2024)
An increased incidence of maternal opioid use disorder (OUD) and neonatal abstinence syndrome (NAS) has prompted recommendations supporting a dyadic approach to care for birthing persons and their infants. However, there are no consensus guidelines outlining how the dyad is clinically defined. To examine how the opioid-exposed birthing person-infant dyad has been defined for purposes of data collection and research, a literature review applying the RAND/UCLA Appropriateness Method was conducted. The search yielded 320 abstracts, with 110 articles identified as having a dyadic focus. While no articles included a specific definition for the dyad, 33 (30%) contained a descriptive reference to the birthing person-infant dyad.Thematic analysis revealed eight recurring elements characteristic of the dyad: 1) engagement, 2) communication, 3) bonding, 4) attachment, 5) mutual responsiveness, 6) reciprocity, 7) synchrony, and 8) attunement. Integrating these elements revealed the interactional relationship between the opioid-exposed birthing person and infant as the foundational principle that defines the dyad. This definition shifts the focus of the opioid-exposed dyad from two individual patient populations to an interactional relationship that has broad applicability for clinical use, public health data collection, and research considerations.